2022
DOI: 10.28926/briliant.v7i3.990
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Perubahan Anatomi Musculus Face Pada Pemberian Paparan Inframerah dengan Akupuntur

Abstract: Relaksasi pada otot wajah dapat melancarkan metabolisme tubuh dan mekanisme otot serta dapat menghilangkan kelelahan. Adanya kelelahan pada wajah memunculkan pengaruh pada anatomi musculus face (otot wajah). Terapi untuk mengurangi kelelahan yang tampak pada musculus face dapat berupa terapi inframerah dan akupuntur. Penelitian ini membandingkan diantara kedua jenis terapi tersebut. Metode yang digunakan yaitu deskriptif analitik. Populasi terdiri dari pasien yang mengalami kelelahan. Sampel diperoleh dari 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 3 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…6 all samples showed a change in relaxation of 60%. Changes in facial muscle relaxation can be seen from changes in the disappearance of wrinkles on the face and forehead, the face looks brighter and the facial muscles feel more elastic when held (Wahyuningtyas et al, 2015) (Soekanto et al, 2022) (Spaskova, 2018) (Smith et al, 2020). Table 2 above was carried out on 15 sample people using acupuncture on facial muscles for 30 minutes twice a week and for 2 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…6 all samples showed a change in relaxation of 60%. Changes in facial muscle relaxation can be seen from changes in the disappearance of wrinkles on the face and forehead, the face looks brighter and the facial muscles feel more elastic when held (Wahyuningtyas et al, 2015) (Soekanto et al, 2022) (Spaskova, 2018) (Smith et al, 2020). Table 2 above was carried out on 15 sample people using acupuncture on facial muscles for 30 minutes twice a week and for 2 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The acupuncture method has the effect of being a natural analgesic and relaxing the body (Hutto & Vattoth, 2015). Previous research looking at changes in the anatomy of the facial muscles after giving infrared therapy and acupuncture found that the facial muscles relax and appear more supple and elastic (Soekanto et al, 2022). In women aged 40-50 years who are experiencing the premenopausal phase, muscle elasticity, and elasticity begin to decrease due to a decrease in the hormone estrogen.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations